2003
DOI: 10.1074/jbc.m305584200
|View full text |Cite
|
Sign up to set email alerts
|

Oma1, a Novel Membrane-bound Metallopeptidase in Mitochondria with Activities Overlapping with the m-AAA Protease

Abstract: The integrity of the inner membrane of mitochondria is maintained by a membrane-embedded quality control system that ensures the removal of misfolded membrane proteins. Two ATP-dependent AAA proteases with catalytic sites at opposite membrane surfaces are key components of this proteolytic system. Here we describe the identification of a novel conserved metallopeptidase that exerts activities overlapping with the m-AAA protease and was therefore termed Oma1. Both peptidases are integral parts of the inner memb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
149
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 141 publications
(155 citation statements)
references
References 53 publications
6
149
0
Order By: Relevance
“…This was consistent with the notion of membrane stress responses; abnormal membrane proteins are expected to be attacked from both sides of the membrane. Kaser et al (31) reported recently that a membrane-bound metalloprotease called Oma1 functions in the degradation of a mitochondrial membrane protein in conjunction with Yta10/12, a mitochondrial homolog of the FtsH protease. Unlike HtpX, Oma1 was reported to cleave a substrate membrane protein on both sides of the membrane.…”
Section: Discussionmentioning
confidence: 99%
“…This was consistent with the notion of membrane stress responses; abnormal membrane proteins are expected to be attacked from both sides of the membrane. Kaser et al (31) reported recently that a membrane-bound metalloprotease called Oma1 functions in the degradation of a mitochondrial membrane protein in conjunction with Yta10/12, a mitochondrial homolog of the FtsH protease. Unlike HtpX, Oma1 was reported to cleave a substrate membrane protein on both sides of the membrane.…”
Section: Discussionmentioning
confidence: 99%
“…Although some proteases appear to exert regulatory functions during mitochondrial biogenesis, a role for others in quality control is just emerging. These include the metallopeptidase Oma1, which was originally discovered in yeast to cleave a mutant IM protein in the absence of the m-AAA protease and was thus termed Oma1 because of its overlapping activity with the m-AAA protease (Käser et al 2003). Oma1 is evolutionarily conserved and is also found in higher eukaryotes, although a role in turnover/processing of misfolded proteins substrates has not yet been assigned.…”
Section: Mitochondrial Quality Controlmentioning
confidence: 99%
“…OMA1 was identified in yeast as an ATP-independent zinc metalloprotease that locates at mitochondrial inner membrane and displays activities overlapping with a m-AAA protease [12]. OMA1 is a mitochondrial quality control protease and was reported as a new key regulator of metabolic homeostasis [13].…”
Section: Introductionmentioning
confidence: 99%